Obraz nadawcy w "Dziennikach" Stefana Kisielewskiego = The image of the sender in Stefan Kisielewski`s "Diaries" - Malon, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article characterizes the means by which the senders in "Diares" by Stefan Kisielewski make themselves present and identifies the communication roles by which the author reveals himself. The analysis of the material showed that the genre restrictions are not an obstacle and allow the author to take on various communication roles (mainly the role of a political whistleblower, a chronicler-historian, a mocker and an ironist) as well as open up the possibility of self-creation.
Keywords: komunikacja; role komunikacyjne; dziennik; autokreacja; communication; communication roles; diary; self-creation